2021
DOI: 10.1111/1467-9817.12353
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding the academic language of complex text: an intervention for late secondary students

Abstract: BackgroundLate secondary‐level students (those in their final 2 years of secondary school) preparing for the demands of university and careers increasingly face texts written in academic language. Unfortunately, few intervention studies show how instruction can improve their reading achievement.MethodsThe 152 student participants (16–17 years old, U.S. Grade 11) were randomly assigned either to small groups receiving scaffolded instruction while reading complex texts or to a business‐as‐usual control condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Indeed, Karasinski (2016) demonstrated that skill in evaluating syntax was uniquely related to understanding science texts, beyond other aspects of language skills. Similarly, instruction in syntax combined with that in scaffolding text structure was connected to improved understanding of academic texts (Reynolds, 2021).…”
Section: A Causal Connection For Syntactic Skills In the Development Of Reading Comprehension?mentioning
confidence: 99%
“…Indeed, Karasinski (2016) demonstrated that skill in evaluating syntax was uniquely related to understanding science texts, beyond other aspects of language skills. Similarly, instruction in syntax combined with that in scaffolding text structure was connected to improved understanding of academic texts (Reynolds, 2021).…”
Section: A Causal Connection For Syntactic Skills In the Development Of Reading Comprehension?mentioning
confidence: 99%
“…Studies that included students with a disability or ELLs were required to provide additional information regarding the school setting. Ten studies met this requirement by providing additional information, such as the percentage of the school population receiving special education services or describing the type of program for ELLs or students with a disability (Bemboom & McMaster, 2013; Clarke et al, 2017; Gorard et al, 2014, 2015; O’Connor et al, 2017; Reynolds, 2021; Swanson et al, 2017; Vaughn et al, 2012, 2015; Williams & Vaughn, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…O’Connor et al (2017) included students who received special education services and reported the percentage of identified disabilities within this group. Reynolds (2021) was the only study that did not describe a disability or the risk status of the participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this view, the target text is the apex of the text set's design. This view connects to a larger line of instructional research on defining features of complex texts and preparing students with cognitive strategies and instructional support to handle the linguistic and conceptual challenges of reading such text (Amendum et al, 2018;Lupo, et al, 2019;Mesmer et al, 2012;Reynolds, 2021). Theoretically, text complexity as an explicit goal could help strengthen students' cognitive reading abilities and build them as lifelong readers.…”
Section: The Goal: Knowledge and Text Complexitymentioning
confidence: 87%